2021
DOI: 10.1093/jac/dkab352
|View full text |Cite
|
Sign up to set email alerts
|

Current and future perspectives in the treatment of multidrug-resistant Gram-negative infections

Abstract: Microbial resistance is a serious threat to human health worldwide. Among the World Health Organisation’s list of priority resistant bacteria, three are listed as critical—the highest level of concern—and all three are Gram-negative. Gram-negative resistance has spread worldwide via a variety of mechanisms, the most problematic being via AmpC enzymes, extended-spectrum β-lactamases, and carbapenemases. A combination of older drugs, many with high levels of toxicity, and newer agents are being used to combat mu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
57
0
6

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 68 publications
(65 citation statements)
references
References 120 publications
(186 reference statements)
2
57
0
6
Order By: Relevance
“…In addition, we found that two ESBL E. coli strains and five CRECL strains were resistant to ertapenem. Inappropriate empiric antibiotic use may be one of the risk factors for MDR ( Bassetti and Garau, 2021 ). This may bring new challenges in the treatment of FRI in the future.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, we found that two ESBL E. coli strains and five CRECL strains were resistant to ertapenem. Inappropriate empiric antibiotic use may be one of the risk factors for MDR ( Bassetti and Garau, 2021 ). This may bring new challenges in the treatment of FRI in the future.…”
Section: Discussionmentioning
confidence: 99%
“…Newer β-lactam/β-lactamase inhibitor combinations (cefepime-zidebactam, cefepime-tazobactam, ceftolozane-tazobactam, ceftazidime-avibactam, meropenem-vaborbactam, imipenem-relebactam, etc.) are now available for clinical use [ 3 , 37 ]. Moreover, the combinations polymyxin B/amikacin, polymyxin B/tigecycline, and polymyxin B/meropenem are promising for treatment of carbapenem-resistant E. cloacae [ 38 , 39 ].…”
Section: Discussionmentioning
confidence: 99%
“…Nonetheless, we must mention one of the newest cephalosporins, cefiderocol, which was inserted into the list of antimicrobials suitable for MDR Gram-negative infections, mainly for MDR Acinetobacter baumannii (39). As Bassetti et al remarked in their review, in Europe, it has been used since 2020, while in the United States it was already approved in 2019 (39). Given its high costs and its initial no-refunds policy in Italy, it was not used routinely.…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, cefiderocol showed advantageous clinical cure rates compared to the best available therapy in Gram-negative pneumonia caused by carbapenem-resistant Enterobacteriaceae, complicated urinary tract infections, bloodstream infections, and sepsis. Despite this, the all-cause mortality was found higher in patients treated with cefiderocol (39). Therefore, its use is restricted to those aged equal to or more than 18 years old with no other options (39).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation